How Did K-pop Take Over the World? (2021)
Today K-pop has become a global phenomenon; present in the lives of millions of people around the world. Beyond being a musical genre, it is considered as a cultural revolution originating in South Korea that has spread to every corner of the planet, strategically designed by the Korean government to elevate the country and its culture as important figures on the international stage. How have they achieved this? The response to this phenomenon is due to a key combination of political and technological changes, a competitive industry, control of the media, and to a great extent the development of artistic talent under a unique formula.